POLYGENIC RISK SCORES PREDICT HYPERTENSION ONSET AND CARDIOVASCULAR RISK. (April 2021) - Vaura, Felix; Kauko, Anni; Suvila, Karri; Havulinna, Aki; Mars, Nina; Salomaa, Veikko; Cheng, Susan; Niiranen, Teemu
Abstract: Objective: We aimed to quantify the predictive ability of polygenic risk scores in hypertension and demonstrate that they improve a gold standard clinical risk score of hypertension in the general population. Design and method: Our study sample comprised N = 218, 792 FinnGen Study participants with lifetime follow-up (mean age 58 years, 56% women). We used recently developed Bayesian methodology and publicly available genome-wide association data to compute polygenic risk scores (PRS) for systolic (SBP) and diastolic blood pressure (DBP). Next, in a well-phenotyped subset of 22, 624 FINRISK study participants, we calculated the 4-year clinical risk of hypertension and 10-year clinical risk of cardiovascular disease (CVD) using gold standard risk scores. Using time-to-event analysis, we then assessed (1) the association of blood pressure PRSs with hypertension, age of hypertension onset, and CVD in all FinnGen participants, and (2) the incremental improvement in model discrimination when combining blood pressure PRSs with the 4-year and 10-year clinical risk predictions of hypertension and CVD in the FINRISK cohorts. Results: Compared to having an average PRS, elevated PRS was associated with up to 2.3-fold risk of hypertension and an 11-year earlier disease onset (Figure). In subgroup analyses, the risk was only 1.6-fold for late-onset hypertension (age > = 55 years), whereas it was 2.8-fold for early-onset hypertension (age < 55 years). Elevated SBP PRS was also associated with up to 1.3-fold risk of CVD and a 4-year earlier disease onset. SBP and DBP PRSs improved clinical risk prediction for hypertension, increasing the C-statistic by 0.7% (0.3–1.1; P = 0.0017) and generating a category-free Net Reclassification Improvement of 9.3% (1.9–16.8; P = 0.014). Inclusion of blood pressure PRSs did not improve the clinical CVD risk score. Figure. No caption available. Conclusions: We demonstrated that genetic information improves clinical risk prediction of hypertension. Blood pressure PRSs could be used together with traditional risk factors to improve prediction of hypertension and particularly early-onset hypertension, which confers substantially increased CVD risk. When used independently, PRSs offer a simple and increasingly affordable way to measure genetic predisposition to hypertension at any point in life. Individuals with elevated blood pressure PRSs could benefit from genetic counseling and intensive early intervention.